Czech Republic: Role and Importance of State Aid and Subsidies - Tomášková, Eva; Radvan, Michal (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
State aid and subsidy policy in the Czech Republic, especially the manner in which the country’s subsidy policy is aligned with regulations of the EU law, form the topic of discussion in this chapter. Direct aid and indirect aid are the two categories of aid covered under the subsidy policy, which has been a subject of much debate in Czech society. The first issue deals with the very essence of state subsidies, that is, whether the benefits of state incentives outweigh their disadvantages. The second is whether the rules are appropriately established for specific incentives and, for example, whether the incentive amount is adequate. The Office for the Protection of Competition and the Ministry of Agriculture and Fisheries monitors, coordinates, and controls state aid. Several entities exploited the advantages offered by state subsidies, although the provision of some subsidies was highly controversial. During the COVID-19 crisis, 18 COVID programmes were offered as the Czech Republic required substantial recovery of the economy and societal conditions. Further, during Russia’s invasion of Ukraine, the energy crisis loomed, making it necessary to resolve this largely through green and digital transitions. A separate chapter is dedicated to fiscal state aid. State aid also provides an advantage through a reduction of the company’s tax burden. These advantages can be used in varied ways, depending on the specific tax. However, despite several reservations (including a certain administrative complexity), these subsidies did contribute to developing the investment environment in the Czech Republic and offered opportunities for financing a wide range of products, such as project plans of towns and municipalities, small- and medium-sized enterprises, and non-profit organisations. Keywords: state aid on the Czech Republic, Czech subsidy policy, COVID-19 period, Russia-Ukraine war period, Czech fiscal state aid